Lack of fire and insect herbivory constrain recruitment in a rare legume from Western Australia. (9th July 2019) - Cochrane, Anne; Monks, Leonie
Abstract: We investigated factors influencing recruitment in the rare endemic shrub Acacia insolita subsp. recurva (Fabaceae) from the heavily cleared south‐west of Western Australia. We examined annual seed production over 4 years, including the impact of herbivory on reproductive output. Conversion of bud to fruit was low (overall 0.02%). The lack of significant difference in canopy dimensions between caged and uncaged plants suggested that vertebrate herbivore grazing was negligible, but invertebrate predation had a negative impact on seed production (loss of >80% of fruiting potential). Soil cores determined the presence of soil‐stored seeds and an experimental burn confirmed that plants are fire‐killed and can regenerate from the seed bank. This seed reserve was found to contain <5 seeds m −2, and both freshly collected seeds and seeds retrieved from the soil had high viability (99% vs . 91%) when subjected to a germination test. Seedling recruitment 29 months post‐fire resulted in a ratio of three seedlings for every adult killed by fire. We also compared reproductive success in this rare Acacia with its common conspecific and although the rare species produced more flowers, the success of flowering did not translate into better fruit set. We conclude that insect damage to reproductive branchlets and lack of appropriate disturbance are major factors constraining recruitment. Active site management may be required for the continued persistence of this fire‐dependent legume.